From management to leadership: A critical analysis of the impacts of COVID-19 on organisational leadership within UK’s consumer industry - Sachdeva, Kanupriya (2022)
The focus of this dissertation is to explore how COVID-19 influenced organizational leadership practices of managers in the UK’s consumer industry while tackling the crisis of the pandemic and its effects on businesses. It unravels how managers adapted to changes and developed leadership qualities, whether intentionally or unintentionally, as a tool to equip themselves to perform better in leading their workforce teams through the challenging effects of the pandemic. It details how they adapted to overcome crisis situations by developing leadership qualities while working during the pandemic. The nine participants chosen for this study belonged to the consumer industry within the UK serving the retail, food production and food distribution sectors as these were the few businesses still running through lockdowns and other restrictive guidelines. The study was conducted qualitatively to support participant experience and narratives using in-depth semi-structured interviews. The interviews lasted for about 30 minutes and were conducted both online and in-person. The majority of the participants (six out of nine) were chosen from the same organization at various hierarchical positions ranging from middle management to senior management, in order to maintain sufficient depth in research. The research question of this study aims to understand which qualities and skills managers needed to practice and develop in order to lead their organization successfully through the pandemic. As a result of answering the over-arching research question, a few research sub-questions that this study explores from the participants’ viewpoint are: a) What changes occurred within the senior managers and/or middle managers’ roles during Covid-19? b) How did the changes that occurred during the pandemic impacted management and/or leadership practices? c) How did subordinates perceive and react to the changes in leadership behaviour of management as a result of Covid-19? d) What practices and skills were perceived to have made a successful and effective leader and why?